Eliminating violence against children (UNICEF New YorkUS, 2007)
Seeks to move states rapidly towards the elimination of all forms of violence against children. Notes that children around the world continue to suffer violence, abuse and exploitation every day. This handbook can enable parliaments and their members to help create a world in which every child can live in safety and with dignity.
Keywords: VIOLENCE